«Propaganda is rejected at school»: the resistance of Norwegian teachers - Odini, Luca (Pensa MultiMedia srl, 2021)
In 1942, during the Nazi occupation of Norway, teachers were intimidated into joining the Nazi Teachers’ League to spread the ideology of the Reich. Eight thousand teachers protested against the threats issued and the authorities responded by imprisoning about a thousand teachers in Kirkenes camp. This led to a collective mobilization: teachers, together with the general population, staged a non-violent protest that forced the government into returning the imprisoned teachers to their classes. This contribution aims to highlight how this particular event constituted a paradigmatic moment in which awareness of the collective responsibility to safeguard free education as a common heritage for human formation emerged clearly among the teachers, society and people of Norway. Nel 1942, durante l’occupazione nazista della Norvegia, agli insegnanti venne intimato di unirsi alla Lega degli Insegnanti Nazisti, per diffondere l’ideologia del Reich. Ottomila professori protestarono resistendo alle minacce e le autorità risposero imprigionando diverse migliaia di docenti nel campo di Kirkenes. A quel punto la mobilitazione fu collettiva: gli insegnanti, insieme alla popolazione, misero in atto una protesta non violenta che costrinse il governo ad intervenire restituendo i docenti imprigionati alle loro classi. Il contributo si propone di evidenziare come questo evento particolare abbia costituito un momento paradigmatico in cui è emersa chiaramente negli insegnanti, nella società e nella popolazione norvegese la coscienza della responsabilità collettiva nel custodire un’educazione libera come patrimonio comune per la formazione umana.